Digest of Welsh Historical Statistics : tourism, parliamentary elections, social services and crime, 1805-1975 - Williams, John L. 19XX- (UK Data Service, 2001)
This machine-readable version of John Williams' Digest of Welsh Historical Statistics is the result of a collaboration between the Statistical Directorate of the National Assembly for Wales, the History Data Service and the Centre for Data Digitisation and Analysis at Queen's University Belfast. John Williams' Digest of Welsh Historical Statistics is intended to provide a service for those working on the history of modern Wales. It arises from a belief that the quantitative element is a necessary and important part of the historical record; from an awareness that it was an aspect that was particularly inaccessible for scholars of Welsh history; and from a conviction that some encouragement in the use of quantitative material was necessary. It is modelled on the two volumes dedicated to British historical statistics: Mitchell, B.R. and Deane, P. (1962) Abstract of British historical statistics and Mitchell, B.R. and Jones, H.G. (1971) Second abstract of British historical statistics.